Epistolary legacy of Russian orientalists: Unpublished correspondence of A.E. Krymsky and V.F. Minorsky (1904–1925) - R.M. Valeev; O.D. Vasylyuk; R.Z. Valeeva; N.N. Diakov; S.A. Kirillina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevant academic and applied problems of the modern Russian and foreign historiography, source and cultural studies include the following fields: the history of the Russian and Ukrainian oriental studies in the 19th – early 20th centuries, as well as other centers of prerevolutionary Russian and Soviet oriental science, such as in CIS countries; regularities, growth areas, and results of the Asian and African studies; academic, educational, and epistolary legacy of Russian and Ukrainian orientalists. The life and academic legacy of A.E. Krymsky (1871–1942) and V.F. Minorsky (1877–1966), the mentor and his student, – two outstanding representatives of the classic orientalism in Russia, Ukraine, and Europe– reflect the events and landmarks in the history of the global studies of the Muslim East. For many years, these two scholars wrote letters to each other. This paper is a short review of some letters written by A.E. Krymsky and V.F. Minorsky and dating back to the period of 1904–1925. These letters belong to the vast epistolary legacy of the prominent orientalists. They were found in the archival centers of Russia and Ukraine. The paper also contains the texts of several letters written by Professor A.E. Krymsky to his talented student from the Lazarev Institute of Oriental Languages.